Pengaruh Produktivitas Kerja terhadap Kepuasan Masyarakat pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Tanah Datar - Rizal, Jose; Frinaldi, Aldri (Policy, Law and Political Research Center, 2023)
This study aims to determine the degree of impact influence work productivity has on community satisfaction at the Department of Population and Civil Registration of Tanah Datar Regency. In order to achieve this goal, the researchers collected data by distributing questionnaires with a population of 101 people (community). Data processing uses quantitative analysis to determine the effect of work productivity on community satisfaction. Based on the results of the study, it was found that there was a positive influence of work productivity on community satisfaction which had been tested using SPSS ver 16, the work productivity variable (X) on Community Satisfaction (Y) had a significance value of 0.000, which is smaller than 0.05. . And the percentage contribution of the X variable to the Y variable is 77.2%. So from this value, it can be concluded that the higher the work productivity, the higher the community's satisfaction with the work productivity produced by employees. This research was conducted to improve the trust and legitimacy of the government and bureaucracy in the community's.